Effect of Lipopolysaccharide and TNFα on Neuronal Ascorbic Acid Uptake - Veedamali S. Subramanian; Trevor Teafatiller; Anshu Agrawal; Masashi Kitazawa; Jonathan S. Marchant (Mediators of Inflammation)
Vitamin C (ascorbic acid: AA) uptake in neurons occurs via the sodium-dependent vitamin C transporter-2 (SVCT2), which is highly expressed in the central nervous system (CNS). During chronic neuroinflammation or infection, CNS levels of lipopolysaccharide (LPS) and LPS-induced tumor necrosis factor-α (TNFα) are increased. Elevated levels of LPS and TNFα have been associated with neurodegenerative diseases together with reduced levels of AA. However, little is known about the impacts of LPS and TNFα on neuronal AA uptake. The objective of this study was to examine the effect of LPS and TNFα on SVCT2 expression and function using in vitro and in vivo approaches. Treatment of SH-SY5Y cells with either LPS or TNFα inhibited AA uptake. This reduced uptake was associated with a significant decrease in SVCT2 protein and mRNA levels. In vivo exposure to LPS or TNFα also decreased SVCT2 protein and mRNA levels in mouse brains. Both LPS and TNFα decreased SLC23A2 promoter activity. Further, the inhibitory effect of LPS on a minimal SLC23A2 promoter was attenuated when either the binding site for the transcription factor Sp1 was mutated or cells were treated with the NF-κB inhibitor, celastrol. We conclude that inflammatory signals suppress AA uptake by impairing SLC23A2 transcription through opposing regulation of Sp1 and NF-κB factors.